Slip imaging: reducing ambiguity in breast lesion assessment. - Kadour, M; Adams, R; English, R; Parulekar, V; Christopher, S; Noble, J (2010)
Ultrasound elasticity imaging (elastography) is gaining popularity as an adjunct to B-mode ultrasound for breast cancer diagnosis. Cancerous masses are usually stiffer than normal tissue, hence, using elasticity imaging should lead to better differentiation between benign and malignant masses than using B-mode alone. Clinicians assess the mobility of masses on palpation; cancers usually being less mobile. We introduce a method to estimate mobility, called slip imaging and combine it with conventional B-mode and elasticity data. In the reported evaluation on 70 women recalled to a breast assessment clinic, images were scored by three breast radiologists independently. Diagnostic accuracy increased from 75.7% with B-mode alone, to 78.1% when including elasticity imaging, to 80.0% when further including slip imaging. Specificity increased (74.6%:75.4%:82.5% respectively), with an apparent trade-off in sensitivity (77.1%:81.3%:77.1%). We conclude that Slip imaging is potentially a useful adjunct to B-mode and elasticity imaging and should undergo further research and development.